Randomized Controlled Trial of Physical Exercise in Diabetic Veterans With Length-Dependent Distal Symmetric Polyneuropathy - Stubbs, Evan B.; Fisher, Morris A.; Miller, Clara M.; Jelinek, Christine; Butler, Jolene; McBurney, Conor; Collins, Eileen G. (Frontiers in Neuroscience, 2019)
This clinical trial was conducted to determine whether exercise alters peripheral nerve function in diabetic patients with advanced polyneuropathy. Forty-five patients were randomized to four experimental groups: sedentary controls, aerobic exercise, isokinetic strength, or the combination of aerobic-isokinetic strength training. At baseline, immediately following intervention, and again at 12-weeks post-intervention, detailed nerve conduction studies were conducted as a primary outcome measure. At these same intervals, all patients completed as secondary measures quantitative sensory testing, symptom-limited treadmill stress tests, and a Short-Form 36-Veterans questionnaire. Of the 45 patients randomized into this study, 37 (82%) had absent sural nerve responses, 19 (42%) had absent median sensory nerve responses, and 17 (38%) had absent ulnar sensory nerve responses. By comparison, responses from tibial nerves were absent in only 3 (7%) subjects while responses from peroneal nerves were absent in 5 (11%) subjects. Eleven (92%) of 12 patients that had volunteered to be biopsied exhibited abnormal levels of epidermal nerve fiber densities. Exercise, regardless of type, did not alter sensory or motor nerve electrodiagnostic findings among those patients exhibiting measurable responses (ANOVA). There was, however, a modest (p=0.01) beneficial effect of exercise on sensory nerve function (Fisher’s Exact test). Importantly, the beneficial effect of exercise on sensory nerve function was enhanced (p=0.03) during the post-intervention interval. In addition, three of six patients that had undergone exercise intervention exhibited a marked 1.9 ± 0.3-fold improvement in epidermal nerve fiber density. By comparison, none of three sedentary patients whom agreed to be biopsied a second time showed improvement in epidermal nerve fiber density. Compared to baseline values within groups, and compared with sedentary values across groups, neither aerobic, isokinetic strength, or the combination of aerobic-isokinetic strength exercise intervention altered peak oxygen uptake. Patients that underwent aerobic or the combined aerobic-isokinetic strength exercise intervention, however, demonstrated an increase in treadmill test duration that was sustained over the 12-week post-intervention period. A 12-week course of physical exercise, regardless of type, does not alter sensory or motor nerve electrodiagnostic findings. In a subset of patients, aerobic exercise selectively improved sensory nerve fiber function.n